Biomimetic Fenton‐Catalyzed Lignin Depolymerization to High‐Value Aromatics and Dicarboxylic Acids. Issue 5 (6th February 2015) - Zeng, Jijiao; Yoo, Chang Geun; Wang, Fei; Pan, Xuejun; Vermerris, Wilfred; Tong, Zhaohui
Abstract By mimicking natural lignin degradation systems, the Fenton catalyst (Fe3+, H2O2) can effectively facilitate lignin depolymerization in supercritical ethanol (7 MPa, 250 °C) to give organic oils that consist of mono‐ and oligomeric aromatics, phenols, dicarboxylic acids, and their derivatives in yields up to (66.0±8.5) %. The thermal properties, functional groups, and surface chemistry of lignin before and after Fenton treatment were examined by thermogravimetric analysis, pyrolysis–gas chromatography–mass spectrometry, 31P NMR spectroscopy, and X‐ray photoelectron spectroscopy. The results suggest that the Fenton catalyst facilitates lignin depolymerization through cleavage of β‐ether bonds between lignin residues. The formation of a lignin–iron chelating complex effectively depresses lignin recondensation; thus minimizing charcoal formation and enhancing the yield of liquid products.